GAMBARAN TINGKAT STRES PENDERITA DIABETES MELLITUS TIPE II SELAMA PANDEMI COVID-19 - Dede Hidayat; Jumaini Jumaini; Yesi Hasneli N (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Diabetes Mellitus (DM) is a chronic disease characterized by high levels of glucose in the blood (hyperglycemia). DM consists of type I DM and type II DM. Type II DM can be caused by factors of age, gender, occupation or physical activity, and level of education. A person who suffers from DM is at risk of experiencing stress twice as much as someone who does not suffer from DM, especially during the Coronavirus Disease 2019 (Covid-19) pandemic. The purpose of this study was to describe the stress level of patients with type II DM during the Covid-19 pandemic. This type of research is quantitative research with descriptive research design. The research sample amounted to 74 respondents who were taken by purposive sampling technique. Determination of the sample using inclusion criteria and exclusion criteria. The measuring instrument used is the depression anxiety stress scale (DASS) questionnaire. The component taken from the DASS questionnaire is the stres component. The analysis used is univariate analysis which is displayed in the form of a frequency distribution table. The results showed most of the respondents experienced severe stress as many as 27 respondents (36.5%) and none experienced very severy stress. The results of this study are expected to be a source of information for nursing science and it is hoped that health workers at the Rejosari Pekanbaru Health Center are able to provide education to prevent and control the stress experienced by type II DM sufferers during the Covid-19 pandemic.Keywords: Coronavirus disease 2019, DASS, Diabetes mellitus, Stress